Problems of Islamic Religious Education in a Multicultural Environment: Analysis of Challenges and Learning Strategies - Juhairiyah, Juhairiyah; Saiful Hadi; Dina Kamilia; Fenny Erdiyani (Penerbit Hellow Pustaka, 2026)
The problems of Islamic Religious Education are various obstacles that hinder the optimal achievement of the goals of Islamic Religious Education. This study discusses the problems of Islamic Religious Education (PAI) in a multicultural environment and relevant learning strategies to address the challenges of diversity. Islamic Religious Education plays a strategic role in shaping the religious character and tolerant attitudes of students. However, heterogeneous social realities, including differences in culture, language, ethnicity, and even religious practices, often create obstacles in the learning process. This study uses a literature review method with a qualitative descriptive approach through an analysis of various literature related to Islamic education, multiculturalism, and Islamic Religious Education (PAI) learning strategies. The results of the study indicate that the main problems in Islamic Religious Education (PAI) learning in a multicultural environment lie in the learning approach that is still normative and textual, the lack of teacher competency in implementing inclusive learning models, and a curriculum that does not explicitly accommodate multicultural values. This study offers several learning strategies, including the use of a dialogic approach, project-based learning, social case studies, and the integration of digital technology as a learning medium that strengthens the values of tolerance, empathy, and cooperation.